Ginsenoside Rb1 attenuates microglia activation to improve spinal cord injury via microRNA‐130b‐5p/TLR4/NF‐κB axis. Issue 3 (6th August 2020) - Wang, Dan; Zhao, Shixin; Pan, Junwei; Wang, Zhen; Li, Yu; Xu, Xiaoxiao; Yang, Jiahao; Zhang, Xi; Wang, Yisheng; Liu, Ming
Abstract: Ginsenoside Rb1 (GRb1), a major ingredient of ginseng, has been found to be a potential protective agent in spinal cord injury (SCI) and in activated microglia‐induced neuronal injury. This study discovered that GRb1 could facilitate miR‐130b‐5p expression in SCI rats and Toll‐like receptor 4 (TLR4; a crucial player in inflammation) was a potential target of miR‐130b‐5p. Hence, we further investigated whether GRb1 could relieve SCI by reducing microglia‐mediated inflammatory responses and neuronal injury via miR‐130b‐5p/TLR4 pathways. The results showed that GRb1 alleviated SCI through inhibiting neuronal apoptosis and proinflammatory factor expression via increasing miR‐130b‐5p.GRb1 weakened the damage of activated microglia to neurons through upregulating miR‐130b‐5p. miR‐130b‐5p attenuated activated microglia‐induced neuron injury via targeting TLR4. GRb1 inactivated TLR4/nuclear factor‐κB (NF‐κB) activation and inhibited proinflammatory cytokine secretion by increasing miR‐130b‐5p in activated microglia. As a conclusion, GRb1 alleviated SCI through reducing activated microglia‐induced neuronal injury via miR‐130b‐5p/TLR4/NF‐κB axis, providing a deep insight into the molecular basis of GRb1 in the treatment of SCI. Abstract : Ginsenoside Rb1 (GRb1) ameliorated locomotor dysfunction, attenuated activated microglia‐mediated proinflammatory responses, and inhibited neuron apoptosis induced by activated microglia through increasing miR‐130b‐5p expression and preventing Toll‐like receptor 4/nuclear factor‐κB (TLR4/NF‐κB) pathway activation.